Magnetic resonance imaging–guided phase 1 trial of putaminal AADC gene therapy for Parkinson's disease. Issue 5 (26th March 2019) - Christine, Chadwick W.; Bankiewicz, Krystof S.; Van Laar, Amber D.; Richardson, R. Mark; Ravina, Bernard; Kells, Adrian P.; Boot, Brendon; Martin, Alastair J.; Nutt, John; Thompson, Marin E.; Larson, Paul S.
Abstract : Objective: To understand the safety, putaminal coverage, and enzyme expression of adeno‐associated viral vector serotype‐2 encoding the complementary DNA for the enzyme, aromatic L‐amino acid decarboxylase (VY‐AADC01), delivered using novel intraoperative monitoring to optimize delivery. Methods: Fifteen subjects (three cohorts of 5) with moderately advanced Parkinson's disease and medically refractory motor fluctuations received VY‐AADC01 bilaterally coadministered with gadoteridol to the putamen using intraoperative magnetic resonance imaging (MRI) guidance to visualize the anatomic spread of the infusate and calculate coverage. Cohort 1 received 8.3 × 10 11 vg/ml and ≤450 μl per putamen (total dose, ≤7.5 × 10 11 vg); cohort 2 received the same concentration (8.3 × 10 11 vg/ml) and ≤900 μl per putamen (total dose, ≤1.5 × 10 12 vg); and cohort 3 received 2.6 × 10 12 vg/ml and ≤900 μl per putamen (total dose, ≤4.7 × 10 12 vg). (18)F‐fluoro‐L‐dihydroxyphenylalanine positron emission tomography (PET) at baseline and 6 months postprocedure assessed enzyme activity; standard assessments measured clinical outcomes. Results: MRI‐guided administration of ascending VY‐AADC01 doses resulted in putaminal coverage of 21% (cohort 1), 34% (cohort 2), and 42% (cohort 3). Cohorts 1, 2, and 3 showed corresponding increases in enzyme activity assessed by PET of 13%, 56%, and 79%, and reductions in antiparkinsonian medication of –15%, –33%, and –42%, respectively, at 6 months. At 12 months, there were dose‐related improvements in clinical outcomes, including increases in patient‐reported ON‐time without troublesome dyskinesia (1.6, 3.3, and 1.5 hours, respectively) and quality of life. Interpretation: Novel intraoperative monitoring of administration facilitated targeted delivery of VY‐AADC01 in this phase 1 study, which was well tolerated. Increases in enzyme expression and clinical improvements were dose dependent. ClinicalTrials.gov Identifier: NCT01973543 Ann Neurol 2019;85:704–714